Pelatihan, Pendampingan, dan Klinikal Penulisan Pentigraf Siswa SMP dan SMA Al Umanaa - Koko, Supriatnoko; Mustofa, Anwar; Rosalina, Erlyn (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2023)
The activity of writing short stories at the Al Umanaa Modern Islamic Boarding School is a class assignment as well as a task outside the classroom in order to strengthen students' skills. It is just that it could not be finished in a short time because it was constrained by the dense school and boarding school activities. On that basis, the community service team carried out the activity of writing short stories for students called three-paragraph short stories, with the aim of helping students to produce short stories in a relatively short time. This activity was carried out effectively for eight days from 02−11 August 2022 with students from class IX, X, XI, and XII. The methods used are face-to-face, lecture, and question-answer methods, followed by the practice of writing three paragraph short story, namely in Indonesian and English, also mentoring and clinical assistance during the students carrying out the writing process. The three paragraphs short story, namely writing activity went very smoothly. They individually were able to write three texts of paragraphs short stories, chosen with different themes as the final target of the activity. The output of this community service activity is in the form of a pentagraph book written by a Boarding School student which is published, has an ISBN, and has recorded intellectual property rights. Kegiatan menulis cerita pendek di SMP dan SMA Al Umanaa menjadi tugas pelajaran di kelas juga menjadi tugas di luar kelas sebagai salah satu keterampilan para siswanya. Hanya saja tidak dapat selesai dalam waktu singkat karena terkendala oleh padatnya kegiatan sekolah dan pesantren. Atas dasar itu, tim pengabdian melaksanakan kegiatan menulis cerita pendek kepada para siswa yang disebut pentigraf, yaitu cerita pendek tiga paragraf, dengan tujuan untuk membantu siswa dapat menghasilkan cerita pendek dalam waktu yang relatif singkat. Kegiatan ini dilaksanakan efektif empat hari dengan peserta siswa kelas IX, X, XI, XII. Metode yang digunakan adalah metode penyuluhan dengan teknik ceramah, tanya jawab, percontohan, dan dilanjutkan dengan praktik menulis pentigraf dalam bahasa Indonesia dan bahasa Inggris, serta pendampingan dan klinikal selama siswa melaksanakan proses penulisan. Kegiatan penulisan pentigraf berjalan dengan sangat lancar. Sekitar 70% dari peserta kegiatan mampu menghasilkan tiga naskah pentigraf dengan tema berbeda. Luaran dari kegiatan pengabdian ini berupa buku pentigraf karya siswa SMP dan SMA Al Umanaa yang diterbitkan oleh sebuah lembaga penerbit.